PENGARUH ATURAN DAN HUKUMAN TERHADAP MANAJEMEN TINGKAH LAKU TARUNA PADA SEKOLAH KEDINASAN - Sukarwoto Sukarwoto; Muhammad Caesar Akbar; Narel Eka Padanta Surbakti (Lafadz Jaya Publisher, 2023)
This study was conducted on the basis of the existing problems at the Medan Aviation Polytechnic which showed that there are still some cadres who have not been disciplined in implementing the order in the institution of the Medan aviation polytechnic, while other case studies can be raised. The author only limits the case studies taken such as the most frequent and highly highlighted because involving the discipline of the taruna itself is there are still tarunas who arrive late in participating in activities in the Medan Aviation Polytechnic environment. Taruna was still indifferent to the school's order. This study aims to determine whether there is an effect between the application of order and punishment on taruna conduct in the Medan Aviation Polytechnic. with this research it is hoped that readers will be able to understand and provide an overview of both disciplinary and disciplinary attitudes that occur and exist in the field of semi-military education The research method used is a survey method with a quantitative approach. The sampling technique is purposive sampling. The research instrument used is a picket with multiple choice forms. The results of this study show that there is a significant influence between the influence of order and punishment on taruna's conduct.